Indications for endoscopic ultrasonography (EUS)‐guided biliary intervention: Does EUS always come after failed endoscopic retrograde cholangiopancreatography?. Issue 2 (10th November 2016) - Nakai, Yousuke; Isayama, Hiroyuki; Yamamoto, Natsuyo; Matsubara, Saburo; Kogure, Hirofumi; Mizuno, Suguru; Hamada, Tsuyoshi; Takahara, Naminatsu; Uchino, Rie; Akiyama, Dai; Takagi, Kaoru; Watanabe, Takeo; et al.
Abstract : Background and Aim: Endoscopic ultrasonography‐guided biliary drainage (EUS‐BD), first reported as an alternative to percutaneous transhepatic biliary drainage (PTBD) after failed endoscopic retrograde cholangiopancreatography (ERCP), is increasingly reported as a primary procedure without failed ERCP. The present study aims to evaluate the outcomes of therapeutic biliary ERCP and to compare the safety and effectiveness of primary EUS‐BD with those of ERCP, rescue EUS‐BD and PTBD. Methods: We retrospectively studied therapeutic biliary ERCP as well as subsequent rescue PTBD and EUS‐BD. Additionally, indications, safety and technical success of primary EUS‐BD were evaluated. Results: Between August 2013 and September 2015, a total of 520 therapeutic biliary ERCP with a native papilla were analyzed. We encountered 23 cases with inaccessible papilla and 22 cases with failed cannulation, which were rescued by 21 PTBD, 16 EUS‐BD and two repeat ERCP. Additionally, 40 primary EUS‐BD were carried out during the same period as a result of 10 recurrent cholangitis cases after transpapillary drainage, five outside failed cannulation, four altered anatomy, two history of ERCP‐related adverse events (AE), two technical difficulties in stenting under enteroscopy‐assisted ERCP and 17 on study protocol. Technical success and AE rates were 95.6% and 14.5% in ERCP, 90.5% and 33.3% in rescue PTBD, 93.8% and 18.8% in rescue EUS‐BD, and 95.0% and 22.5% in primary EUS‐BD, respectively. Conclusions: Rescue EUS‐BD was used in 3.1% among all ERCP. Given the comparable technical success and AE rates of both primary and rescue EUS‐BD, primary EUS‐BD without failed ERCP can be a treatment option if it provides advantages over ERCP.